Il pentimento in Tolstoj e Dostoevskij. Dal cerchio magico dell’Io al bisogno di perdono - Giuseppe Ghini (Linguae &: Rivista di Lingue e Culture Moderne, 2014)
Given the religious metaphysics of Russian Realism (Steiner 1995: 49), repentance is one of the pivotal moments necessary for the characters of Tolstoy’s and Dostoevsky’s works: it is through repentance that such characters radically change their lives, become aware of evil committed, and renounce evil forever; in other words, they die and are reborn. The two great novelists have, however, two very different attitudes towards repentance: Tolstoy examines all its aspects in the psychological consciousness of his characters, while Dostoyevsky shows their necessary openness to the transcendent world.